Information Connectivity as A Primary Instrument to Enhance Transport Connectivity - Nugroho, Setyo; Zaman, Muhammad Badrus; Murdjito,; Djatmiko, Eko Budi; Busse, Wolfgang (International Journal of Marine Engineering Innovation and Research, 2025)
Remotely located islands posses their own unique beauties and their common challenges. A case study on Maratua to enhance the quality of life is perceived to be achieved through the enhancement of the transport connectivity. The physical connectivity is manifested in the form of transport connectivity, entails the availability and the ease of obtaining a transport service to transfer goods and people. Deeper efforts to understand the mechanism of obtaining a transport service entails a primary actor directing both the ship and cargoes or passengers. This actor is the information connectivity. The paper elaborates promising efforts towards managing the information connectivity as a key for enhancing the transport service.